Pengembangan Sistem Layanan Pengajuan Surat Warga Pada Kelurahan Sukun Di Kota Malang - Rizky Aditya Arifin; Denny Sagita Rusdianto; Adam Hendra Brata (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
One of the strategies applied by the Sukun Malang Village in filing citizen letters is by submitting citizen letters online. Submission of citizen letters online is very necessary because there are many residents who submit letters to the kelurahan. Sukun Urban Village has several submissions of citizen letters implemented on the system. However, the system still cannot overcome the problems that exist and is only done in the Sukun Malang Village, but not for RT and RW. The problem is a long process when residents submit a citizen letter with the number of residents who make submissions and submissions that are currently being carried out are still using a lot of paper. So that a system is needed to overcome these problems, namely submitting citizen letters online. This system is used to submit citizen letters, see details of letters submitted by residents, verify submission letters submitted by residents and print a letter of submission. The results of the analysis in this study obtained 58 functional requirements and 1 non-functional requirement from 5 actors who had roles in the system. In this study functional testing was carried out using white box and black box methods by conducting unit testing, integration and validation. The results of unit testing produce 100% valid values for 3 functional requirements tested, then the results of integration testing produce 100% valid values for 3 functional requirements tested and for validation test results produce 100% valid values for all functional requirements which means the system already in accordance with the needs analysis. In non-functional testing using compatibility testing, the system is expected to be used in different development environments or in browsers such as Google Chrome, Mozilla Firefox, Internet Exlporer, Microsoft Edge and Opera.